Aquatic Pollution in the Bay of Bengal: Impacts on Fisheries and Ecosystems - Nowrin Akter Shaika; Saleha Khan; Sadiqul Awal; Md. Mahfuzul Haque; Abul Bashar; Halis Simsek (Hydrology, 2025)
Aquatic pollution in the Bay of Bengal has become a major environmental issue with long-term impacts on fisheries, biodiversity, and ecosystems. The review paper examines the major pathways, sources, and ecological consequences of aquatic pollution in the Bay of Bengal. Pollutants such as heavy metals, pesticides, petroleum hydrocarbons, and microplastics have been reported at concerning levels in the soil and water in aquatic ecosystems. Rivers act as key routes, transporting pollutants from inland sources to the Bay of Bengal. These contaminants disrupt metabolic and physiological functions in fish and other aquatic species and pose serious threats to food safety and public health through bioaccumulation. Harmful algal blooms (HABs), caused by nutrient enrichment, further exacerbate ecosystem degradation in the Bay of Bengal. The review highlights the immediate need for strengthened pollution control regulations, real-time water quality monitoring, sustainable farming practices, and community-based policy interventions to preserve biodiversity and safeguard fisheries.